High Temperature Resistant Coatings for Strategic Aero space Applications - Alam, Zafir; Parlikar, Chandrakant; Kumawat, Mahesh; Lakshmi, S. Gokul; Das, Dipak (Defence Science Journal, 2023)
The aerospace components operating in hot sections of aero-engines and combustors experience extreme environments. Typically, the components are subjected to high service temperatures exceeding 1100°C and oxidizing conditions. Protective coatings are essential for preventing oxidation-induced dimensional degradation of the components and enhancing their high temperature capability as well as durability. Defence Metallurgical Research Laboratory (DMRL) has developed a variety of metallic and ceramic thermal barrier coating (TBC) systems for Ni-base superalloys, and refractory Nb-alloys for strategic aerospace applications involving ultra-high temperatures and high flow velocities. These coatings have demonstrated significant effectiveness against thermal degradation at temperatures as high as 2000 °C during oxidation in static air as well as in dynamic conditions involving high flow velocities (Mach > 2). The present article provides an overview of the advanced oxidation resistant and thermal barrier coatings developed in DMRL. The effectiveness of the TBCs in preventing dimensional degradation of the metallic and composite substrate materials has been evaluated at the laboratory scale. The developed TBCs have the potential for use in aero-engines and propulsion systems of hypervelocity vehicles.